It's a very merry Muppet Christmas movie [videorecording (DVD)] - Thatcher, Kirk R.; Arquette, David; Cusack, Joan, 1962-; Lillard, Matthew, 1970-; Macy, William H., 1950-; Goldberg, Whoopi, 1955-; Whitmire, Steve, 1959-; Goelz, Dave; Barretta, Bill; Oz, Frank (Muppets Studio, LLC ; Universal Studios Home Entertainment, 2010)
Join Kermit the Frog, Fozzie Bear, Gonzo, Miss Piggy and the entire Muppet gang. 'Tis the night before Christmas and the Muppet Theater is in danger of being torn down. When bad goes to worse, Kermit begins to believe that the world would be a better place if he had never been born. With heavenly help and hilarious send-ups of just about every holiday movie ever made, Kermit and the Muppets discover what matters most is their love for each other.